Abstinence-contingent wage supplements to promote drug abstinence and employment: a randomised controlled trial. Issue 5 (21st February 2020) - Holtyn, August F; Toegel, Forrest; Subramaniam, Shrinidhi; Jarvis, Brantley P; Leoutsakos, Jeannie-Marie; Fingerhood, Michael; Silverman, Kenneth
Abstract : Background: Poverty, unemployment and substance abuse are inter-related problems. This study evaluated the effectiveness of abstinence-contingent wage supplements in promoting drug abstinence and employment in unemployed adults in outpatient treatment for opioid use disorder. Methods: A randomised controlled trial was conducted in Baltimore, MD, from 2014 to 2019. After a 3-month abstinence initiation and training period, participants (n=91) were randomly assigned to a usual care control group that received employment services or to an abstinence-contingent wage supplement group that received employment services plus abstinence-contingent wage supplements. All participants were invited to work with an employment specialist to seek employment in a community job for 12 months. Abstinence-contingent wage supplement participants could earn training stipends for working with the employment specialist and wage supplements for working in a community job, but had to provide opiate and cocaine-negative urine samples to maximise pay. Results: Abstinence-contingent wage supplement participants provided significantly more opiate and cocaine-negative urine samples than usual care control participants (65% vs 45%; OR=2.29, 95% CI 1.22 to 4.30, p=0.01) during the 12-month intervention. Abstinence-contingent wage supplement participants were significantly more likely to have obtained employment (59% vs 28%; OR=3.88, 95% CI 1.60 to 9.41, p=0.004) and lived out of poverty (61% vs 30%; OR=3.77, 95% CI 1.57 to 9.04, p=0.004) by the end of the 12-month intervention than usual care control participants. Conclusion: Abstinence-contingent wage supplements can promote drug abstinence and employment. Trial registration number: ClinicalTrials.gov NCT02487745 .